A new species of Hisonotus (Siluriformes, Loricariidae) from rio Sao Francisco basin, Brazil - Roxo, Fabio F. [UNESP]; Silva, Gabriel da C. e [UNESP]; Oliveira, Claudio [UNESP] (Pensoft Publ, 2015)
A new species of Hisonotus is described from the rio Sao Francisco basin. The new species can be distinguished from congeners by having (1) a unique coloration pattern of caudal fin with one black spot extending from its origin to the ventral lobe and two dark spots at the end of the lobe's rays; (2) odontodes forming longitudinally aligned rows on head and trunk; (3) a functional V-shaped spinelet; (4) a single rostral plate at the tip of the snout; (5) by lacking contrasting dark geometric spots on the anterodorsal region of the body; (6) a lower caudal-peduncle depth; and (7) lower counts of the lateral median plates and (8) higher premaxillary and dentary teeth. The new species is the second described species of the genus Hisonotus in the rio Sao Francisco basin. It was found inhabiting the marginal vegetation of the rio Sao Francisco and three of its tributary, rio das Velhas, rio Paraopeba and rio Formoso.
Keywords: Cascudinhos; Fresh-Water; Minas Gerais State; Neotropical Fish; Otothyrinae